Formation of cross-cultural communicative competence among foreign students during pre-university training - Tazheva, Zalina (2021)
The stage of pre-university training is the most important stage in the professional development of foreigners studying at the preparatory faculties of Russian universities. During this period, cross-cultural communicative competence is being formed.The article proves that the formation of cross-cultural communicative competence is a complex process, which can be facilitated by the concept of its component composition. The article describes the pedagogical conditions that are necessary for the formation of intercultural communicative competence.